Research on the aesthetic characteristics and contemporary reproduction of Chu dance from the perspective of Multicultural Paradox - Tao, Run (International Theory and Practice in Humanities and Social Sciences, 2025)
As a treasure of ancient Chinese culture and art, “Chu Dance” holds a unique position in the history of ancient Chinese dance development and is one of the important contents of Chu studies. From the perspective of multicultural paradox, this article analyzes the aesthetic characteristics of Chu dance and its reappearance in contemporary Chinese dance creation.